Kajian Yuridis Tentang Putusan Verstek Dalam Perkara Cerai Talak Di Pengadilan Agama Bondowoso Kelas 1A: (Studi Kasus Perkara No. 0015/Pdt.G/2020/Pa/Bdw.) - Alfina Wildatul Fitriyah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2020)
Every human being in this world has a dream of a peaceful and peaceful home and even aging with a partner forever, no one wants their marriage to break up halfway either couples who are still not blessed with children or who already have children. But in the household does not escape the emergence of various problems that can result in disputes that are difficult to reconcile until finally divorce becomes the final way, as happened to the Bondowoso Class 1A Religious Court with a divorce case with a verstek verdict. The purpose of this study is to analyze the ratio decidendi of judges in Handing down Verstek Verdict No. 0015/Pdt.G/2020/PA.Bdw. and to find out the legal consequences regarding the wife's rights due to divorce talaq verstek. This research uses descriptive field research with a qualitative approach method. The types and sources of this research data are primary data sources and secondary data. The data collection techniques used were observation, interviews and documentation. The results of this study can conclude that the juridical study of the verstek decision in the talaq divorce case at the Bondowoso Religious Court class 1A is based on considerations based on a summons (relaas), the Defendant has been formally and properly summoned according to law and in accordance with the provisions of Article 26 of Government Regulation No. 9 of 1975 but does not appear at the conference and does not represent to others as his attorney. In his absence, the judge held that the defendant had waived his rights, as well as from the provisions of Article 19 letter (f) of Government Regulation No. 9 of 1975 Jo Article 116 letter (f) of the Compilation of Islamic Law.